EVALUATION OF DIFFERENT PRE-SETTING CONDITIONS IN AIRLIFT BIOREACTOR TO DETERMINE THE RESPIRATORY KINETICS OF FUNGI - Rossi, MJ; Cortez, DH Cardoso; Giachini, AJ; Oliveira, VL; Jr, A Furigo (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2015)
in culture media and, therefore, used to obtain large volumes of fungal tissue to be used as inoculum. The implementation of controlled mycorrhization programs is dependent upon the production of commercially large volumes of inoculum. As of now, there is no such place around the globe where we can find people or companies that are able to achieve such goal. Information on the fungal growing kinetics is scant, and there are no studies that deal with the topic of oxygen transfer for the cultivation of these fungi (major impediment), making it hard to produce inoculum in large scales. Therefore, the current study used an airlift bioreactor to provide information on aspects, such as time of mixture, the effect of depressurization on the oxygen concentration readings and the delay of probe response, among others, that are fundamental for the commercial production of these fungal inocula. The study showed that the results obtained from the dynamic assay need adjustments prior to analytical interpretation. The data was obtained with operating specific air flow rates of 0.2, 0.36 and 0.52 vvm. In conclusion, the study provided essential information that can be used by others to continue the studies on the dynamic aspects of an airlift bioreactor operation intended for fungal biomass production.